The three temples : on the emergence of Jewish mysticism - Elior, Rachel (Littman library of Jewish civilization (Series), 2004)
In this ground-breaking study, Rachel Elior offers a comprehensive theory of the crystallization of the early stages of the mystical tradition in Judaism based on the numerous ancient scrolls and manuscripts published in the last few decades. Her wide-ranging research, scrupulously documented, enables her to demonstrate an uninterrupted line linking the priestly traditions of the Temple, the mystical liturgical literature found in the Qumran caves and associated directly and indirectly with the Merkavah tradition of around the second and first centuries BCE, and the mystical works of the secon.